2021
DOI: 10.29050/harranziraat.886982
|View full text |Cite
|
Sign up to set email alerts
|

Beç tavuğu etinin kimyasal ve yağ asidi kompozisyonu üzerine yetiştirme sistemi ve kesim yaşının etkisi

Abstract: Beç tavuğu etinin kimyasal ve yağ asidi kompozisyonu üzerine yetiştirme sistemi ve kesim yaşının etkisi Effect of production system (intensive and free-range), and slaughter age on chemical and fatty acid composition of meat in guinea fowl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…Similarly to the present study, Tejerina et al (2009) reported significant differences in dry matter, protein, and fat content between breast and thigh muscles ( P ≤ 0.05). Boz et al (2021) also noted considerable differences in the chemical composition of breast and thigh muscles from 16-wk-old, free-range guinea fowl, although the difference in fat content was only 0.37% (1.89% in the present study). In the current study, the dry matter content of the evaluated muscles was similar, but the content of protein and ash was higher than in the cited studies.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…Similarly to the present study, Tejerina et al (2009) reported significant differences in dry matter, protein, and fat content between breast and thigh muscles ( P ≤ 0.05). Boz et al (2021) also noted considerable differences in the chemical composition of breast and thigh muscles from 16-wk-old, free-range guinea fowl, although the difference in fat content was only 0.37% (1.89% in the present study). In the current study, the dry matter content of the evaluated muscles was similar, but the content of protein and ash was higher than in the cited studies.…”
Section: Resultscontrasting
confidence: 58%
“…In guinea fowl, the greatest differences have been observed in the protein content of breast muscles, which ranged from 22.8% in 6-mo-old females ( Musundire et al, 2017 ) to 23.48% in 12-wk-old females ( Tufarelli and Laudadio, 2015 ) or even 27.5% in 1-yr-old males ( Musundire et al, 2017 ). The protein content of leg muscles is less varied, ranging from 19.66% in 16-wk-old, free-range guinea fowl and 20.38% in 16-wk-old birds raised in an intensive system ( Boz et al, 2021 ) to 21.26% in 16-wk-old guinea fowl reared indoors ( Pudyszak et al, 2005 ) and 21.89% in 16-wk-old, free-range lavender guinea fowl ( Śmiecińska et al, 2022 ). In turn, the IMF content of breast muscles was determined in the range of 0.21% ( Śmiecińska et al, 2022 ) to 0.84% ( Pudyszak et al, 2005 ) and 2.09% in 12-wk-old guinea fowl broilers fed faba beans ( Tufarelli and Laudadio, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the chemical composition of the breast and leg muscles of guinea fowl confirmed that they had high protein content and low fat content [ 9 ]. Boz et al [ 41 ] analyzed the chemical composition of breast muscles in 16-week-old guinea fowl, partridges, and pheasants reared in free-range and intensive systems and noted significant differences ( p ˂ 0.05) between bird species, whereas the effect exerted by the farming system was not significant ( p > 0.05). In the cited study, the content of dry matter (26.38%), fat (0.26%), and ash (0.99%) in the breast muscles of guinea fowl was similar to the values determined in this experiment, whereas protein content was more than 2% lower.…”
Section: Discussionmentioning
confidence: 99%
“…In the cited study, guinea fowl were raised indoors on deep litter, which could contribute to increased fat deposition in their carcasses due to limited physical movement, compared with birds that had access to outdoor space. Boz et al [ 41 ] reported that only the dry matter content of thigh muscles varied depending on guinea fowl’s age ( p ˂ 0.05), whereas the effect exerted by production system was not significant ( p > 0.05). In the above study, the thigh muscles of guinea fowl reared in a free-range system had similar dry matter content (24.31%), and a lower content of protein (19.66%), fat (0.66%), and ash (0.86%), compared with the values noted in this experiment.…”
Section: Discussionmentioning
confidence: 99%